Overexpression of Drosophila Rad51 protein (DmRad51) disrupts cell cycle progression and leads to apoptosis. - Yoo, S.; McKee, B.D. (Chromosoma, 2004)
Among proteins involved in homologous recombination, Rad51 is an essential enzyme in DNA repair and recombination. However, little is known about its role in cell cycle regulation and apoptosis. To examine the function of Drosophila Rad51 (DmRad51) in cell cycle regulation and apoptosis, DmRad51 protein was overexpressed using a heat shock-inducible promoter or the UAS-GAL4 binary expression system. We observed that ubiquitous expression of DmRad51 protein in flies carrying hsp26- Rad51 or UAS- Rad51 transgenes was lethal. Induction of DmRad51--more specifically in eye or wing imaginal discs--caused tissue-specific cell death in the domains of DmRad51 expression. Cell death was due to apoptosis, as shown by staining with the TdT-mediated dUTP nick-end labeling assay. Immunocytochemistry revealed that cells expressing DmRad51 colocalized with apoptotic cells. In addition, the phenotypes caused by the overexpression of DmRad51 were similar to those caused by ectopic expression of Reaper, a proapoptotic protein, and were partially suppressed by the coexpression of p35, an antiapoptotic protein. Using an antiphosphohistone H3 antibody, we also observed that the overexpression of DmRad51 protein disrupted normal cell cycle progression in eye imaginal discs. Taken together, these results show that ectopically expressed DmRad51 disrupts cell cycle regulation and induces apoptosis.